2005
DOI: 10.1038/sj.onc.1209230
|View full text |Cite
|
Sign up to set email alerts
|

Id proteins: Novel targets of activin action, which regulate epidermal homeostasis

Abstract: Activin is a member of the transforming growth factor b (TGF-b) family, which plays a crucial role in skin morphogenesis and wound healing. To gain insight into the underlying mechanisms of action, we searched for activin-regulated genes in cultured keratinocytes. One of the identified target genes encodes Id1, a negative regulator of helix-loop-helix transcription factors. We show that Id1, Id2, and Id3 are strongly downregulated by activin in keratinocytes in vitro and in vivo. To determine the role of Id1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
2
31
1
Order By: Relevance
“…TGF-␤ has been observed to repress expression of the Id transcription factors in epithelial cells (32). In contrast, we found that TGF-␤ treatment of CA46 BL cells readily induced expression of Id1 and Id2, indicating that this may be an example of cell type differences in the TGF-␤ response.…”
Section: Discussioncontrasting
confidence: 51%
“…TGF-␤ has been observed to repress expression of the Id transcription factors in epithelial cells (32). In contrast, we found that TGF-␤ treatment of CA46 BL cells readily induced expression of Id1 and Id2, indicating that this may be an example of cell type differences in the TGF-␤ response.…”
Section: Discussioncontrasting
confidence: 51%
“…Although all HaCaT-cyclin clones were still able to stratify, detailed analysis of the differentiation process demonstrated deregulation of the well-ordered sequential expression particularly of the late differentiation markers. This phenotype was unexpected because it was observed neither in vectortransfected control cells used in this or previous studies nor after transfection with other oncogenes including Ha-ras or c-myc (Boukamp et al, 1990;Cerezo et al, 2003;Rotzer et al, 2006). This strongly excludes clonal variation of the HaCaT population as being causal for this phenotype, but suggests a very specific and novel role of cyclin D1 in this process.…”
Section: Cyclin D1 Overexpression Alters Proliferationmentioning
confidence: 69%
“…Furthermore, p63 is crucial for the activation of the epithelial cell adhesion program (47) or to maintain the proliferative potential of stem cells (48). Taking into account the well-established roles of ID2 in controlling epidermal homeostasis and cell fate in human keratinocytes (13)(14)(15)(16), including its capacity to inhibit differentiation (6,32,49) the regulatory link that we observe between p63 and ID2 seems particularly interesting. Indeed, as it was recently suggested in an excellent review on epidermal homeostasis (50) that the identification of key genes downstream of p63 would provide important new insights into its roles in dynamic equilibrium of differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…The anti-proliferative effect of retinoids on human keratinocytes seems to result from the down-regulation of ID2 gene expression through a transcriptional convergence between Wnt and retinoid signaling (14). Transforming growth factor ␤ (TGF␤) also inhibits growth of epithelial cells, including keratinocytes, through long term repression of ID2 and ID3 (15,16). Similarly ID2 promotes tumor cell proliferation via control of cyclin D1 protein level (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation